Oxido-Reductive Stress and Alcoholic Liver Disease - Kołota, Aleksandra; Gromadzka-Ostrowska, Joanna (Medical and Biological Sciences, 2014)
Due to availability and relatively low price, alcohol is currently the most widely used intoxicant. Consuming excessive amounts of alcohol is associated with multiple health consequences, which include pathological changes in the liver leading to development of alcoholic liver disease. Responsible for the formation of the mentioned changes are among others: metabolic disorders, immune reactions and formation of cytokines, hypoxia of hepatocytes in the perivenular area of hepatic lobule and oxido-reductive stress. The aim of this paper is to present the mechanism of the oxido-reductive stress associated with long-term alcohol abuse. The knowledge and understanding of the mechanisms underlying this phenomenon may help to avoid the negative effects of alcohol consumption, before development of severe liver damage, induced by toxic effects of alcohol.